Peculiarities of men's adaptation potential under the force loads effects - O. V. Yermishev; T. A. Kuchenko; D. J. Shevchuk (Kazimierz Wielki University, 2020)
We studied the problems of improving sports and fitness classes in strength fitness to increase the adaptive capacity of the body of untrained young men aged 20-21 years old by using different load regimes. In the analysis of scientific and methodological literature, it was found that the methodology and the impact of loads on adaptation processes are not comprehensively studied. In addition, effective and at the same time safe load regimens using various exercises in sports and recreation are not developed to the full extent. To study the impact of strength training, 20 untrained people were invited. They used two load modes: Group 1 - standard level and Group 2 - high-intensity and low-volume mode. As a result of the analysis of the obtained indicators of adaptive potential in the 1st group, which were recorded during 3 months of training under power loads, the optimal period of duration of significant adaptive changes in their body, which intensified after the second month of training, was determined. The analysis of lean body weight shows an increase relative to the second month not only in the 1st group, but no significant changes were recorded in the 2nd group. The analysis of the results of the comprehensive body size of young men in both untrained groups show almost identical parameters. The level of coverage in the participants of the 1st group is on average 8.9% lower compared to the results obtained in the 2nd group. Based on the results obtained, we can say that the most informative markers for assessing adaptive changes in the body of men with a low level of physical fitness are morphometric parameters of the body.